2011
DOI: 10.1139/z11-083
|View full text |Cite
|
Sign up to set email alerts
|

Testing climate-based species distribution models with recent field surveys of pond-breeding amphibians in eastern Missouri

Abstract: Species distribution models (SDMs) have become an important tool for ecologists by providing the ability to predict the distributions of organisms based on species niche parameters and available habitat across broad geographic areas. However, investigation of the appropriate extent of environmental data needed to make accurate predictions has received limited attention. We investigate whether SDMs developed with regional climate and species locality data (i.e., within Missouri, USA) produce more accurate predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Our results add to the body of evidence on the relevance of ecological niche models for predicting local and regional occurrence of species within their native ranges (Trumbo et al 2011;Peterman et al 2013), and in novel environments (Gormley et al 2011;Vaclavik and Meentemeyer 2012). While climate alone may oversimplify the spatial extent of invasions, ecological niche models for patchily-distributed generalist species are a reliable alternative to using data intensive methods that require substantial resources and foresight.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our results add to the body of evidence on the relevance of ecological niche models for predicting local and regional occurrence of species within their native ranges (Trumbo et al 2011;Peterman et al 2013), and in novel environments (Gormley et al 2011;Vaclavik and Meentemeyer 2012). While climate alone may oversimplify the spatial extent of invasions, ecological niche models for patchily-distributed generalist species are a reliable alternative to using data intensive methods that require substantial resources and foresight.…”
Section: Discussionmentioning
confidence: 58%
“…4), the rank correlation between the two predictions is informative. Focusing on an area in eastern Missouri, Trumbo et al (2011) evaluated the accuracy of ecological niche models compared to estimates from single detection/ non-detection surveys for nine amphibian species, and found that six of nine species (including L. clamitans) had high congruence, while three species showed a weak or no congruence (including L. catesbeianus). These results were apparent in the spatial predictions of invasion extent, where ecological niche models based on data from both the native and invaded range overestimated suitability for L. catesbeianus at our occupancy survey sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this promising scenario, we highlight some topics relating anuran physiological ecology to climate that remain understudied and that can contribute to amphibian conservation. Phenology and dormancy: Amphibians usually link reproduction to environmental cues, and therefore may have their phenology impacted by climate change (Beebee 1995, Blaustein et al 2001, Trumbo et al 2011). Indeed, a recent review lists phenological shifts among several key nonacute lethal impacts of climate change on amphibians (Li et al 2013).…”
Section: Amphibian Physiological Ecology In the Context Of Climate Chmentioning
confidence: 99%
“…Amphibians, being ectothermic, are also sensitive to extreme overwinter climatic conditions (Tattersall and Ultsch 2008). For example, populations of the Columbia spotted frog are expected to enjoy increased viability due to improved survivorship and reproduction associated with milder winters brought by climate change (McCaffery and Maxell 2010), and yet occupancy predictions from species distribution models are unreliable at spatial scales relevant for amphibian conservation (Trumbo et al 2011). Development of detailed, mechanistic models like that developed here to help understand constraints on amphibian range expansion may help predict distribution changes for these species, which are some of the most vulnerable to climate change (Lawler et al 2009).…”
Section: Applicationsmentioning
confidence: 99%